Visualization and user interactions in RDF data representation - Babenko, Vasily (My University, 2021)
The spreading of linked data in digital technologies creates the need to develop new approaches to handle this kind of data. The modern trends in the information technology encourage usage of human-friendly interfaces and graphical tools, which helps users to understand the system and speeds up the work processes. In this study my goal is to develop a set of best practices for solving the problem of visualizations and interactions with linked data and to create a working prototype based on this practices. My work is a part of a project developed by Fail-Safe IT Solutions Oy. During the research process I study various existing products that try to solve the problem of human-friendly interactions with linked data, compare them and based on the comparison develop my own approach for solving the problem in the given environment, which satisfies the provided specifications. The key findings of the research can be grouped in two categories. The first category of findings is based on the existing solution examinations and is related to the features I find beneficial to the project. The second category is based on the experience acquired during the project development and includes environment-specific and project-related findings.
Keywords: RDF, linked data, user experience, graphical interfaces, interactions, web interface, JavaScript, React